ВИКОРИСТАННЯ ІНТЕРАКТИВНИХ МЕТОДІВ НАВЧАННЯ У ПІДГОТОВЦІ МАЙБУТНІХ ВЧИТЕЛІВ ДО ПЕДАГОГІЧНОЇ ВЗАЄМОДІЇ З УЧНЯМИ (Педагогіка вищої та середньої школи, 2022)
In article the approaches to students' preparing to the pedagogical co-operation with pupils have been considered. Theeffectiveness of using interactive methods and ways of professionally significant features of future teachers forming process.